Special Review Section: Children's Picturebooks About Libraries. Issue 4 (1st October 2016) - Orcutt, Darby; Wiseman, Angela
ABSTRACT: As librarians, and especially collections-focused librarians, we almost daily face misperceptions and misunderstandings of libraries, of our work, and of the collections and services that we provide. From outdated ideas, to stereotypes, to incomplete images of the realities and value of our institutions and our profession, these representations may pose constant challenges and consternation. In this special review section, my colleague Dr. Angela Wiseman, Associate Professor of Education and an expert on children's books, joins me in reviewing a sampling of current children's books about libraries.